1998
DOI: 10.1093/emboj/17.14.3921
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ binding to synaptotagmin: how many Ca2+ ions bind to the tip of a C2-domain?

Abstract: C 2 -domains are widespread protein modules with diverse Ca 2⍣ -regulatory functions. Although multiple Ca 2⍣ ions are known to bind at the tip of several C 2 -domains, the exact number of Ca 2⍣ -binding sites and their functional relevance are unknown. The first C 2 -domain of synaptotagmin I is believed to play a key role in neurotransmitter release via its Ca 2⍣ -dependent interactions with syntaxin and phospholipids. We have studied the Ca 2⍣ -binding mode of this C 2 -domain as a prototypical C 2 -domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
362
1
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 289 publications
(395 citation statements)
references
References 46 publications
24
362
1
5
Order By: Relevance
“…The C2A domain exhibits a similar conformational change in limited proteolysis experiments (Davletov and Südhof 1994). These changes may reflect the movement of charged residues within or near the Ca 2+ -binding loops (Ubach et al 1998b; Chae et al 1998), as indicated by structural studies of the C2 domain of phospholipase C-δ1 (Grobler et al 1996). Given the diffusion-limited kinetics of the C2 domains of synaptotagmin, these conformational changes are unlikely to involve large-scale structural rearrangements (Davis et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The C2A domain exhibits a similar conformational change in limited proteolysis experiments (Davletov and Südhof 1994). These changes may reflect the movement of charged residues within or near the Ca 2+ -binding loops (Ubach et al 1998b; Chae et al 1998), as indicated by structural studies of the C2 domain of phospholipase C-δ1 (Grobler et al 1996). Given the diffusion-limited kinetics of the C2 domains of synaptotagmin, these conformational changes are unlikely to involve large-scale structural rearrangements (Davis et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…(A) Schematic diagram of putative Ca 2+ ligands within the C2B domain of synaptotagmin I. This model is based on structural studies of a variety of C2 domains (Sutton and Sprang 1995; Sutton et al 1995; Grobler et al 1996; Perisic et al 1998; Ubach et al 1998a,Ubach et al 1998b) and alignments between the C2A and C2B domains of synaptotagmin. (B) Wild-type (WT) and the indicated synaptotagmin Ib point mutants were analyzed for Ca 2+ -triggered oligomerization activity as described in Fig.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Together they provide Ca 2+ coordination for up to four potential Ca 2+ -binding sites labeled sites I-IV; however, in a given C2 domain only a subset of the four sites may actually bind Ca 2+ in solution, since not all the sites provide adequate Ca 2+ coordination. Thus, the Ca 2+ -loaded C2 domains characterized to date possess from one to three Ca 2+ bound in different combinations of sites I-IV (12,15,(17)(18)(19).…”
mentioning
confidence: 99%